2017
DOI: 10.1074/jbc.m116.763813
|View full text |Cite
|
Sign up to set email alerts
|

Iso-α-acids, Bitter Components of Beer, Prevent Inflammation and Cognitive Decline Induced in a Mouse Model of Alzheimer's Disease

Abstract: Edited by Luke O'NeillAlongside the rapid growth in aging populations worldwide, prevention and therapy for age-related memory decline and dementia are in great demand to maintain a long, healthy life. Here we found that iso-␣-acids, hop-derived bitter compounds in beer, enhance microglial phagocytosis and suppress inflammation via activation of the peroxisome proliferator-activated receptor ␥. In normal mice, oral administration of iso-␣-acids led to a significant increase both in CD11b and CD206 doublepositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 37 publications
1
100
0
Order By: Relevance
“…Specific and significant preventive action against Alzheimer disease from hops' iso-α-acids, which are responsible for bitterness in beer, was recently argued along with its potentially deep social impact with rapidly ageing populations worldwide (Ano et al, 2017). Moreover, evidence has arisen for anti-carcinogenic action from hops' prenil-flavonoids (Ferk et al, 2010;Karabin et al, 2015; Ż ołnierczyk et al, 2015), as well as from phenolic constituents extracted from both malt and hop (Ferk et al, 2010;Gerhäuser, 2005).…”
Section: Beer a Healthy Food?mentioning
confidence: 99%
“…Specific and significant preventive action against Alzheimer disease from hops' iso-α-acids, which are responsible for bitterness in beer, was recently argued along with its potentially deep social impact with rapidly ageing populations worldwide (Ano et al, 2017). Moreover, evidence has arisen for anti-carcinogenic action from hops' prenil-flavonoids (Ferk et al, 2010;Karabin et al, 2015; Ż ołnierczyk et al, 2015), as well as from phenolic constituents extracted from both malt and hop (Ferk et al, 2010;Gerhäuser, 2005).…”
Section: Beer a Healthy Food?mentioning
confidence: 99%
“…Among other substances, hop's iso-α-acids were recently attributed specific and significant preventive action against the Alzheimer disease (Ano et al, 2017), as well as beer was estimated as one of the richest sources of silicon in the diet, which is important for the growth and development of bone and connective tissue (Casey & Bamforth, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, even though it is the most-consumed alcoholic beverage, no constituents of beer had been demonstrated to have preventive effects on dementia. However, a recent study using a rodent model has now shown that intake of ingredients in beer has preventive effects on Alzheimer's disease pathology [9]. These ingredients are iso-α-acids, the hop-derived bitter components of beer.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, iso-α-acids were identified as novel components regulating microglia [9], a type of immune cell in the nervous systems. As a regulator of the immune response in the brain, microglia have been recently attracting increasing attention because numerous reports suggest that inflammation in the brain severely induces cognitive decline and exacerbates Alzheimer's disease pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation